Social Capital in Moneylenders Phenomenon in Blimbing Traditional Market Malang Indonesia - Hidayati, Bunga; Yamamoto, Naoyuki; Kano, Hideyuki; Suman, Agus; Manzilati, Asfi (International Journal of Economics and Financial Issues, 2017)
A moneylender is a person who lends money at excessively high rates of interest. The moneylender is called loan shark. The reality shows that moneylender is still an important capital source for merchants. The aim of this research is to know the role of social capital (network, trust, and norm) on moneylender phenomenon. By using phenomenology, the result shows that: (1) Social capital makes merchants prefer using moneylender than formal financial institutions. (2) The more personal relationship that is part of a network makes moneylender is friendlier than the formal financial institution. (3) The intensity of interaction creates trusts that can substitute collateral. (4) Moneylender behavior which is humanist is accepted by merchants as added value. Keywords: Social Capital, Moneylender, and Merchants JEL Classifications: Z1, Z13, Z130